ANALISIS PENERIMAAN PAJAK RETRIBUSI TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA BATAM 2015-2019 - Zahara Fatimah (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2020)
The aim of research is to know and analysis the influence of retrubution taxes and retribution fact fund to local revenue in batam city. Sample is used are the region’s in come official period 2015-2019.The sampling technique in this study using saturated sampling technique.Methods data analysis in this research is quantitative methods the result of research to shows that local taxes is significant effect to local revenue is caused significant value for 0,000 < 0,05, local retribution is significant effect to local revenue with significant value 0,000 < 0,05, while the local taxes and local retribution fund together are significant effect to local revenue with significant effect 0,000 < 0,05. R square value to shows the variable of local taxes and local retribution fund can to explain variable variance of local revenue for 99,6% while the remaining is 0,4% is effected by the other variable is not researched